Analisa Pemahaman Konsep Matematika Siswa pada Materi Trigonometri Kelas X SMK Asisi - Margaretha Silvia; Indra Martha Rusmana; Endang Suhendar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study aims to describe the understanding of mathematical concepts of X grade students of SMK ASISI on Trigonometry material. The type of research is descriptive qualitative research. the subjects are 3 students of class X AKL SMK ASISI who have high, medium and low categories, these students were selected on the basis of the results of daily test scores. This study refers to 5 indicators of understanding of mathematical concepts and the instruments in this study are written tests and interviews. Based on the results of the analysis, it can be concluded that students' understanding of mathematical concepts in trigonometry material is still relatively low and students have not met the indicators of understanding mathematical concepts from the results obtained from 12 students, there are 1 student who gets high scores, 7 students get medium scores, and 4 students get low scores.